Physiological variability and in vitro antifungal activity against Botrytis cinerea causing botrytis gray mold of chickpea (Cicer arietinum L.) - Hosen, M. I.; Ahmed, A. U.; Islam, M. R. (Spanish Journal of Agricultural Research, 2010)
Physiological variability was studied in 10 isolates of Botrytis cinerea causing botrytis gray mold of chickpea, collected from diverse agro climatic areas in Bangladesh. The optimum temperature and pH for the best mycelial radial growth of B. cinerea were 20°C and 4.5, respectively. The mycelial radial growth increased with the temperature up to 20°C thereafter it decreased gradually up to 30°C and no growth was observed at 35°C. Chickpea dextrose agar (CDA) medium supported the highest mycelial radial growth (79.17 mm). The quickest (in 5 days) sclerotia initiation was recorded on chickpea destrose agar and lentil dextrose agar (LDA) culture media while the highest number of spores (2.5104 mL–1) were recorded on LDA medium. The antagonist Trichoderma harzianum was found to be a good bio-control agent against B. cinerea. Among the seven fungicides Bavistin® 50 WP (Carbendazim), CP-Zim 50 WP (Carbendazim), Sunphanate 70 WP (Thiophanate methyl) and Rovral 50 WP (Iprodione) were the most effective to inhibit the mycelial radial growth of B. cinerea at 500 mg L–1 concentration.